Effects of Dietary Fat Source on Performance of Lactating Dairy Cows Fed a Pre-mixed Concentrate - C. Ylioja; C. Abney-Schulte; Rick A Stock; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2015)
Inclusion of a pre-blended concentrate (OneTrak®, Cargill Inc., Blair, NE) in the total mixed ration (TMR) for dairy cows can simplify the daily mixing of dietary ingredients. A cow’s response to fat supplementation can be affected by other dietary ingredients; however, little is known about production responses to dietary fat in diets with high concentrations of non-forage fiber. This study evaluated cow performance in response to fat sources when the ration contained a pre-blended concentrate composed largely of a non-forage fiber source. Six pens of mid-lactation cows were studied; the addition of saturated fat (Energy Booster 100) and rumen-protected unsaturated fat (Megalac) were compared to a control diet with no added fat. Milk yield tended to increase with both fat sources. Protein concentration decreased with fat supplementation but protein yield did not differ. Efficiency of conversion of feed to milk tended to increase for Megalac compared with Energy Booster. These responses to dietary fat are comparable to those for diets without OneTrak®, suggesting that no unusual dietary interactions with fat supplements are apparent with OneTrak® feeding programs.
Keywords: fat; lactation; nutrition